Is Ross Syndrome a New Type of Synucleinopathy? A Brief Research Report - Ma, Mingming; Yao, Jing; Chen, Yongkang; Liu, Han; Xia, Danhao; Tian, Haiyan; Wang, Xinxin; Wu, Erxi; Wang, Xuejing; Ding, Xuebing (Frontiers in Neuroscience, 2020)
Ross syndrome (RS) is a rare peripheral autonomic system disorder characterized by tonic pupil, hyporeflexia, and segmental anhidrosis. Neuropathological studies show that RS results from the selective cholinergic nerve degeneration. However, the cause and underlying mechanisms are largely unknown. Here, we show that α-synuclein accumulation in the autonomic nerve terminals in the lesser curvature of stomach of patients with RS. In addition, immunohistochemical findings demonstrate that a dominant degeneration of cholinergic fibers exhibits in patients with RS, while main degeneration of adrenergic fibers in patients with pure autonomic failure in their gastrointestinal and urinary system. Our study suggests that RS belongs to α-synucleinopathies. Moreover, our findings indicate that adrenergic nerves and cholinergic nerves are not equally damaged in different types of pure autonomic dysfunctions.